2011
DOI: 10.1007/s00424-011-0995-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Kir channel inhibition by quinacrine: acute pore block of Kir2.x channels and interference in PIP2 interaction with Kir2.x and Kir6.2 channels

Abstract: Cardiac inward rectifier potassium currents determine the resting membrane potential and contribute repolarization capacity during phase 3 repolarization. Quinacrine is a cationic amphiphilic drug. In this work, the effects of quinacrine were studied on cardiac Kir channels expressed in HEK 293 cells and on the inward rectifier potassium currents, I(K1) and I(KATP), in cardiac myocytes. We found that quinacrine differentially inhibited Kir channels, Kir6.2 ∼ Kir2.3 > Kir2.1. In addition, we found in cardiac my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Quinacrine is a molecule developed in the 1920s as anti-malarial agent, based upon the aminoacridine ring structure; more recently, it has been shown to inhibit different ionic currents, like the I A (Kehl, 1991), the L-type Ca 2+ current (Nagano et al, 1996) and the inward rectifier K + current (Evans and Surprenant, 1993; López-Izquierdo et al, 2011). We then tested quinacrine (100 μM), which suppresses a significant fraction of the hyperpolarization-activated current in DA-PG cells (Figure 7B): for voltage commands to -100 mV, the amplitude of the inward current was reduced from −17.16 ± 3.00 pA/pF (CTL) to −12.19 ± 2.98 pA/pF ( p < 0.001; n = 9; Two-Way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinacrine is a molecule developed in the 1920s as anti-malarial agent, based upon the aminoacridine ring structure; more recently, it has been shown to inhibit different ionic currents, like the I A (Kehl, 1991), the L-type Ca 2+ current (Nagano et al, 1996) and the inward rectifier K + current (Evans and Surprenant, 1993; López-Izquierdo et al, 2011). We then tested quinacrine (100 μM), which suppresses a significant fraction of the hyperpolarization-activated current in DA-PG cells (Figure 7B): for voltage commands to -100 mV, the amplitude of the inward current was reduced from −17.16 ± 3.00 pA/pF (CTL) to −12.19 ± 2.98 pA/pF ( p < 0.001; n = 9; Two-Way ANOVA).…”
Section: Resultsmentioning
confidence: 99%
“…IRK2/KCNJ12; (Karschin et al, 1996); also KIR2.3 is weakly expressed in the glomerular layer (Inanobe et al, 2002; Allen Brain Atlas, 2013). Quinacrine, which differentially inhibits the K ir channels (KIR2.3 > KIR2.1 » KIR6.2; (López-Izquierdo et al, 2011), suppresses a large (46%) fraction of hyperpolarization-activated inward current. However, the presence of KIR6.x (a.k.a.…”
Section: Discussionmentioning
confidence: 99%
“…The Kir6.2 subunit has a low apparent affinity for PIP 2 relative to that of other Kir channels, and this property probably underlies a high sensitivity to inhibition by cationic amphiphilic drug (CADs) López-Izquierdo et al, 2011a). Kir6.2(C166S) increases the apparent PIP 2 affinity and renders molpharm.aspetjournals.org channels far less sensitive to rundown induced by PIP 2 depletion (Ribalet et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The order of reported channel sensitivity to CADs is Kir3.1/3.4 Ͼ Kir6.2 Ͼ Kir2.3 Ͼ Kir2.1 (Ponce-Balbuena et al, 2009López-Izquierdo et al, 2011a,b). Recently, we found that quinacrine induced a double action toward Kir channels, i.e., direct pore block of Kir2.1 and Kir2.3 and interference in PIP 2 -Kir channel interaction in a differential manner, Kir6.2 ϳ Kir2.3 Ͼ Kir2.1 (López-Izquierdo et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation